2008
DOI: 10.1007/s11262-008-0311-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of two low pathogenic avian influenza virus H5N1 isolates from Ontario, Canada

Abstract: Genomes of two low pathogenic H5N1 avian influenza (LPAI) viruses, A/Turkey/ON/84/1983 and A/Mallard/ON/499/2005 from Ontario, Canada were cloned and genetically characterized. Phylogenetic analysis showed that the Canadian isolates cluster with other North American AIVs and are distinct from the Euro-Asian H5N1 isolates. Individual gene comparisons demonstrated that the Ontario isolates were most similar to the viruses isolated from around the same time period and geographical area. A long deletion of 22 amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Our speculation coincides with other studies which demonstrated that highly pathogenic H5N1 virus infection in mice model could cause a down-regulation of TGF-β secretion which resulted in more severe and widespread lesions [51]. These may also account for the difference in pathogenicity of different AIV strains [52,53]. …”
Section: Discussionsupporting
confidence: 92%
“…Our speculation coincides with other studies which demonstrated that highly pathogenic H5N1 virus infection in mice model could cause a down-regulation of TGF-β secretion which resulted in more severe and widespread lesions [51]. These may also account for the difference in pathogenicity of different AIV strains [52,53]. …”
Section: Discussionsupporting
confidence: 92%
“…Both Australian and American continents were omitted from the map because of no report of highly pathogenic avian influenza H5N1 outbreaks to date (Pei et al, 2009;Yee et al, 2009). Figure 2a shows the locations of the outbreaks.…”
Section: Datamentioning
confidence: 99%
“…Viruses of the N1, N2, and N3, and less frequently N6 and N7, neuraminidase types that harbor a 20-to 30-amino-acid deletion in the NA stalk have been isolated from domestic poultry (2,4,7,10,13,14,19). Such a deletion was also observed upon experimental transmission to quail or chickens of viruses belonging to the H2N2 (24,25), H7N3 (8), H9N2 (9), and H11N9 (11,12) subtypes.…”
mentioning
confidence: 99%